Potentially Bioaccessible Phenolic and Antioxidant Potential of Fresh and Stored Lentil Sprouts—Effect of Lactobacillus plantarum 299v Enrichment - Urszula Gawlik-Dziki; Barbara Baraniak; Małgorzata Sikora; Anna Jakubczyk; Ireneusz Kapusta; Michał Świeca (Molecules, 2021)
The phenolic and antioxidant potential of potentially bioaccessible fractions of lentil sprouts was studied. Sprouts were cocultivated with a probiotic to obtain a new functional product and further stored in cool conditions. The fraction obtained after buffer extraction and gastric digestion had higher content of phenolics compared to the control (by 20% and 46%, respectively); however, a 9% decrease was observed in samples obtained after gastrointestinal digestion. After gastrointestinal digestion, the highest content of phenolics (278 µg/g d.w.) was determined in the fresh control sprouts. Compounds neutralizing ABTS and hydroxyl radicals, chelating metal ions, and exhibiting strong reducing power were effectively released after gastrointestinal digestion (e.g., the values of the gastrointestinal digestibility index for chelating power and ability to quench hydroxyl radicals significantly exceeded 1 in all studied samples). It was proved that the enrichment of sprouts with a probiotic and further storage significantly improved the antioxidant potential; compared to the fresh control sprouts, an increase by 45% and 10% was determined after the gastric and gastrointestinal digestion, respectively. Lentil sprouts enriched with L. plantarum 299v may be a new functional product characterized by the high antioxidant capacity of the potentially bioaccessible fraction.